First Occurrence of Plasmablastic Lymphoma in Adenosine Deaminase-Deficient Severe Combined Immunodeficiency Disease Patient and Review of the Literature - Migliavacca, Maddalena; Assanelli, Andrea; Ponzoni, Maurilio; Pajno, Roberta; Barzaghi, Federica; Giglio, Fabio; Ferrua, Francesca; Frittoli, Marta; Brigida, Immacolata; Dionisio, Francesca; Nicoletti, Roberto; Casiraghi, Miriam; et al. (Frontiers in Immunology, 2018)
Adenosine deaminase deficient-severe combined immunodeficiency disease (ADA-SCID) is a primary immune deficiency characterized by mutations in the ADA gene resulting in accumulation of toxic compounds affecting multiple districts. Hematopoietic stem cell transplantation (HSCT) from a matched donor and hematopoietic stem cell gene therapy (HSC-GT) are the preferred options for definitive treatment. Enzyme replacement therapy (ERT) is used to manage the disease in the short term, while a decreased efficacy is reported in the medium-long term. To date, eight cases of lymphomas have been described in ADA-SCID patients. Here we report the first case of plasmablastic lymphoma occurring in a young adult with ADA-SCID on long-term ERT, which turned out to be Epstein-Barr virus (EBV) associated. The patient previously received infusions of genetically modified T cells. A cumulative analysis of the 8 published cases of lymphoma from 1992 to date, and the case here described, reveals a high mortality (89%). The most common form is diffuse large B-cell lymphoma, which predominantly occurs in extra nodal sites. Seven cases occurred in patients on ERT and two after haploidentical HSCT. The significant incidence of immunodeficiency-associated lymphoproliferative disorders and poor survival of patients developing this complication highlight the priority in finding a prompt curative treatment for ADA-SCID.